2018
DOI: 10.1055/s-0043-125074
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity Interval Training Frequency: Cardiometabolic Effects and Quality of Life

Abstract: The effects of high intensity interval training (HIIT) frequency on cardiometabolic health and quality of life were examined in 35 healthy inactive adults (age: 31.7±2.6 yrs, VOpeak: 32.7±7.4 ml·: kg ·: min). Participants were randomly assigned to a control (CON) and two training groups, which performed 10×60-s cycling at ~83% of peak power, two (HIIT-2) or three times per week (HIIT-3) for eight weeks. Compared with CON, both training regimes resulted in similar improvements in VOpeak (HIIT-2: 10.8%, p=0.048,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 48 publications
8
41
1
9
Order By: Relevance
“…This suggests that adaptation of aerobic metabolism is an early response to sprint training and that increasing frequency of training has no additional benefits. Such findings are in agreement with a recent study by Stavrinou et al [21], who reported that different high-intensity interval training frequency (two vs. three times per week) similarly affects the magnitude of improvement in VO 2 peak in young, inactive, healthy adults. Furthermore, it has been shown that in young adults, changes in VO 2 max occur within six sprint sessions and then plateau regardless of training volume [25].…”
Section: Predicted Vo 2 Maxsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that adaptation of aerobic metabolism is an early response to sprint training and that increasing frequency of training has no additional benefits. Such findings are in agreement with a recent study by Stavrinou et al [21], who reported that different high-intensity interval training frequency (two vs. three times per week) similarly affects the magnitude of improvement in VO 2 peak in young, inactive, healthy adults. Furthermore, it has been shown that in young adults, changes in VO 2 max occur within six sprint sessions and then plateau regardless of training volume [25].…”
Section: Predicted Vo 2 Maxsupporting
confidence: 93%
“…This suggests that training once a week using sprint interval training would have a significant impact on the health and wellbeing of older adults but doing it more frequently could have greater metabolic health benefits. This is similar to findings in younger, healthy, inactive adults (Age: 31.7 ± 2.6 years) which suggest 3 times a week high-intensity training produced greater metabolic adaptations than training twice weekly [21]. However, we still need to determine if total sprint numbers were the same, would the differences between the training groups still persist.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, as for health-related quality of life, a recent study performed in healthy inactive adults (31.7 ± 2.6 years) reported that a HIIT with low and moderate training frequency (2 and 3 times per week) showed significant improvements in the SF-36 physical health component, but only moderate-intensity training improved the mental component of quality of life [53]. In the present study, we found significant benefits after HIIT compared to both MIIT and CG with regards to the SF-36 domains general health, health changes, vitality and physical functioning, with large size effects (Cohen' d values of 1.13 and .57 respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Apart from sprint duration and number of sprint repetitions, a final approach to reducing the total volume of sprint exercise in a SIT protocol is to reduce the training frequency. A small number of studies investigating the effects of repeated sprint training (RST; repeated 'all-out' sprints of <20 s) (Adamson et al 2014) and high-intensity interval training (HIIT; repeated (sub-)maximal sprints of ≥60 s) (Stavrinou et al 2018) have demonstrated significant improvements in VȮ2max with just 2 training sessions/week for 8 weeks, but to the best of our knowledge, the effect of training frequency on improvements in VȮ2max in response to SIT has not yet been studied. Similar to REHIT, most commonly studied SIT protocols involve a training frequency of 3 sessions/week .…”
Section: Introductionmentioning
confidence: 99%